Mamba's daughters - Heyward, DuBose, 1885-1940 (Salt Lake City, UT : Project Gutenberg, 2025)
"Mamba's Daughters: A Novel of Charleston" by DuBose Heyward is a novel published in 1929. Set in early 20th-century Charleston, it follows three families navigating deception and social transformation against a backdrop of rigid racial boundaries. The story explores the complex connections between Charleston's white elite and its Black working class, offering insight into both racial tensions and an unusual shared subculture. The novel's success led to a groundbreaking 1939 Broadway adaptation starring Ethel Waters, breaking barriers in American theater. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Mamba%27s_Daughters
Release date is 2025-06-02
Susan E., David E. Brown, Mary Fahnestock-Thomas, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Charleston (S.C.) -- Fiction; Domestic fiction; Mothers and daughters -- Fiction; Businesspeople -- Fiction; Race relations -- Fiction; African American women -- Fiction; Women household employees -- Fiction; Women -- South Carolina -- Fiction